2016
DOI: 10.4103/0972-124x.186946
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey to study the relationship of periodontal disease with cardiovascular disease, respiratory disease, and diabetes mellitus

Abstract: Background:Periodontal deterioration has been reported to be associated with systemic diseases such as cardiovascular disease (CVD), diabetes mellitus, respiratory disease, liver cirrhosis, bacterial pneumonia, nutritional deficiencies, and adverse pregnancy outcomes.Aim:The present study assessed the periodontal disease among patients with systemic conditions such as diabetes, CVD, and respiratory disease.Materials and Methods:The study population consisted of 220 patients each of CVD, respiratory disease, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 48 publications
2
20
1
Order By: Relevance
“…Currently, there are no reports on the link of periodontal disease with overall profile of common comorbidities. Several recent studies show that the severity of periodontal destruction is related to multiple systemic conditions, respectively . Other studies deal with the interconnection of one specific comorbidity (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are no reports on the link of periodontal disease with overall profile of common comorbidities. Several recent studies show that the severity of periodontal destruction is related to multiple systemic conditions, respectively . Other studies deal with the interconnection of one specific comorbidity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies show that the severity of periodontal destruction is related to multiple systemic conditions, respectively. [39][40][41][42] Other studies deal with the interconnection of one specific comorbidity (e.g. CVD) to periodontal status with adjustment of other comorbidities as confounders.…”
Section: Discussionmentioning
confidence: 99%
“…About one-half of the adult population suffers from moderate to severe periodontal diseases that are also potentially associated with diabetes mellitus [1]. The hyperglycemic environment promotes the expression of toll-like receptors in periodontal tissues, making diabetic patients more susceptible to periodontitis [2].…”
Section: Introductionmentioning
confidence: 99%
“…Intergroup analysis (ND and D groups) showed greater bone loss in the ND group treated with SRP compared to the D group treated with SRP+SDT.DiscussionPg, as the major pathogenic microorganism, plays an important role in promoting the development and progression of periodontal disease[8]. Previous studies have reported that HMME combined with laser or ultrasound has an antimicrobial effect on whether Gram-positive or Gram-negative bacteria, such as MRSA, Escherichia coli1 2…”
mentioning
confidence: 99%
“…Oral disease, caries [5][6][7] and periodontal disease [6,[8][9][10] are associated with diabetes. Hyperglycaemia over a long period of time and glucose variability may result in chronic inflammation that affects the immune system.…”
Section: Introductionmentioning
confidence: 99%